Vicarious Trial-and-Error Is Enhanced During Deliberation in Human Virtual Navigation in a Translational Foraging Task - Huynh, Thach; Alstatt, Keanan; Abram, Samantha V.; Schmitzer-Torbert, Neil (Frontiers in Behavioral Neuroscience, 2021)
Foraging tasks provide valuable insights into decision-making as animals decide how to allocate limited resources (such as time). In rodents, vicarious trial-and-error (back and forth movements), or VTE, is an important behavioral measure of deliberation which is enhanced early in learning and when animals are presented with difficult decisions. Using new translational versions of a rodent foraging task (the “Movie Row” and “Candy Row”), humans navigated a virtual maze presented on standard computers to obtain rewards (either short videos or candy) offered after a variable delay. Decision latencies were longer when participants were presented with difficult offers, overrode their preferences, and when they accepted an offer after rejecting a previous offer. In these situations, humans showed VTE-like behavior, where they were more likely to pause and/or reorient one or more times before making a decision. Behavior on these tasks replicated previous results from the rodent foraging task (“Restaurant Row”) and a human version lacking a navigation component (“Web-Surf”) and revealed some species differences. Compared to survey measures of delay-discounting, willingness to wait for rewards in the foraging task was not related to willingness to wait for hypothetical rewards. And, smoking status (use of cigarettes or e-cigarettes) was associated with stronger discounting of hypothetical future rewards, but was not well related to performance on the foraging tasks. In contrast, individuals with overweight or obese BMI (> 25) did not show stronger delay-discounting. Finally, on the foraging task, females and male smokers showed reduced sensitivity to sunk-costs (where their decisions were less sensitive to irrecoverable investments of effort) and a weaker sensitivity to the value of offers. These data indicate that VTE is a behavioral index of deliberation in humans, and further support the Movie and Candy Row as translational tools to study decision-making in humans with the potential to provide novel insights about decision-making that are relevant to public health.